From Listeners to Creators: The Potential of Podcasts as a Revolutionary Media for Indonesian Language Learning in Islamic Universities - Nursalim; Kholid Junaidi; M. Rifaldi (Anglophile Journal, 2025)
This research analyzes the perception and impact of using podcasts as a medium for learning Indonesian based on questionnaire data from 187 respondents at four Islamic universities in Riau. The research uses a quantitative descriptive method with a survey approach using purposive sampling techniques. The research results show a very high level of podcast adoption (98.4%) with a positive impact, especially on increasing listening ability (85%), vocabulary mastery (78%), and speaking motivation (91.7%). However, a gap was found between individual interest and institutional support, with 65% of institutions not yet having a podcast- specific policy. Correlation analysis revealed a significant relationship between listening frequency and increased language skills (45%), podcast language quality and speaking confidence (60%), and institutional support and interest in podcast production (3x higher). This research recommends the integration of podcasts in the curriculum, standardization of language quality, and strengthening institutional support to optimize the potential of podcasts in language learning.